THE STONE TOOL-MAKING TECHNIQUES USED BY THE HOABINHIAN INHABITANTS FROM THE LATE PLEISTOCENE TO THE EARLY HOLOCENE: A CASE STUDY OF PIT 3 AT CHO CAVE, HOA BINH PROVINCE - Thanh Son Pham; Gia Doi Nguyen (Tạp chí Khoa học Đại học Đà Lạt, 2024)
The collection of both shaped and unshaped stone tools discovered at Cho Cave during the 2004 excavation has provided new data on an early system of Hoabinhian archaeological sites in northern Vietnam. However, the attributes of unifacial and bifacial flaking techniques in Vietnam and Southeast Asia remain underexplored. This article, in addition to building upon past research data, applies attribute-based research methods to the stone tool assemblage from Pit 3 to investigate the diversity of stone tool production techniques over time. The research findings indicate that from approximately 24,000 to 20,000 cal. BP, both shaped and unshaped tools coexisted. After 20,000 cal. BP, the group of unshaped tools diminished, while the types of shaped tools exhibited greater diversity. The transition from unifacial to bifacial flaking techniques in the shaped tool group is evident at Cho Cave. In the early Holocene, the evolution from flaking techniques to grinding techniques was also recorded. Thus, this study contributes new insights into the emergence of stone tool-making techniques of Hoabinhian residents from the late Pleistocene to the Holocene in Vietnam and Southeast Asia.